Preferences of Pakistani Doctors in Selection of Antibiotics for the Treatment of Uncomplicated Enteric Fever: Ciprofloxacin vs. Meropenem - Azhar, Shazia; Shah, Khuntalha; Zubia Zia, Zubia Zia; Razzak, Mariam; Mary Augustine, Zarnab; Manzoor, Adnan (Indus Journal of Bioscience Research, 2024)
Background: The field of enteric fever therapy has undergone a significant transformation due to the advent of antibiotic resistance (AMR). Amoxicillin, trimethoprim-sulfamethoxazole, and chloramphenicol were once the first-line therapies. However, these choices are no longer as successful due to the emergence of multidrug-resistant (MDR) bacteria. ciprofloxacin, have been the recommended option in recent years because of their oral absorption and potency against vulnerable bacteria. Unfortunately, a reassessment of treatment procedures has been necessitated by reports of significant incidence of fluoroquinolone resistance, particularly in South Asia. The move toward meropenem is indicative of the pressing need for efficient treatments given the rise in resistance. Meropenem is recommended by the World Health Organization to treat severe infections brought on by XDR S. typhi, highlighting its significance in modern treatment protocols. Methodology: It was a cross sectional study conducted at tertiary care hospital of Karachi. The calculated sample size was n=64. All the doctors working in medicine ward and working residents who were in third and fourth year of their residency in medicine were included. A preformed questionnaire was administered to them to identify their preferences. Frequencies and percentages of responses were assessed and compared with chi square and t-test analysis. P-value less than 0.05 was considered as significant. Results: Participants of all the groups responded that they have examined the patients with enteric fever (p-0.001), there was disparity in advising blood test for diagnosis (p-0.098), most of them mentioned they initiate therapy on clinical examination. When asked for the preference between ciprofloxacin and meropenem majority responded in the favor of ciprofloxacin (p-0.001). Conclusion: The doctors preferred choosing ciprofloxacin for uncomplicated enteric fever which is positive indication to preserve the last resort antibiotics such as meropenem.